Cloning and characterisation of genes encoding molecular recognition proteins from insects - Liggins, Amanda (2001)
Olfaction is one of the most important senses by which insects obtain information about their environment. In the early stages of olfactory perception in insects, odour molecules are carried across the sensillum lymph by small soluble Odorant Binding Proteins (OBPs). This is followed by activation of the appropriate olfactory receptor, resulting in an electrical impulse, and subsequent degradation of the initial signal. OBPs have been studied in a range of insect orders including Lepidoptera, Diptera and Orthoptera, and this study reports the cloning and characterisation of cDNAs with a potential olfactory role in the vetch aphid, Megoura viciae (Buckton, Homoptera: Aphididiae). Construction and sequencing of antennal cDNA libraries identified two cDNAs, MvicOBP1 and Mv164, which were approximately 0.8kb and 1kb respectively. The amino acid sequence of MvicOBP1 has the spacing pattern of six cysteine residues that is characteristic of insect OBPs, and Mv164 shows similarity to insect cytochrome P450 enzymes. RT-PCR showed that these cDNAs have specific or enhanced expression in the chemosensory tissues of M. viciae, and parallel expression patterns suggest a "linked" function. Related sequences are present and expressed in other aphid species, and sequencing of genomic fragments allowed the partial elucidation of the intron/exon organisation of these genes. Subtracted antennal cDNA libraries identified two cDNAs encoding proteins with significant similarity to insect chemosensory proteins (CSPs), cDNAs encoding Juvenile Hormone Binding Proteins (JHBPs), and a tissue-specific cDNA with a potential carrier role. These, coupled with the OBPs, add evidence to the suggestion that there is an insect superfamily of binding proteins. A PBP from Bombyx mori (BmorPBP1) was used as a model system for in vitro expression of an insect OBP and subsequent characterisation of the recombinant protein. Four forms of this protein, identified through their interaction with an anti-BmorPBP antibody, were resolved by isoelectric focusing.